African women writers and the politics of gender - Zulfiqar, Sadia (Cambridge Scholars Publishing, 2016)
This work examines the work of a group of African women writers who have emerged over the last forty years. While figures such as Chinua Achebe, Ben Okri and Wole Soyinka are likely to be the chief focus of discussions of African writing, female authors have been at the forefront of fictional interrogations of identity formation and history. In the work of authors such as Mariama Ba (Senegal), Buchi Emecheta (Nigeria), Chimamanda Ngozi Adichie (Nigeria), Tsitsi Dangarembga (Zimbabwe), and Leila Aboulela (Sudan), there is a clear attempt to subvert the tradition of male writing where the female